Global governance of food and agriculture industries : transatlantic regulatory harmonization and multilateral policy cooperation for food safety - Carruth, Reba Anne (Northampton, MA : Edward Elgar, 2006)
This book details the implications of globalisation, free trade and regional market integration on the ability of national governments to regulate food safety in the food and biotechnology sectors.
aug 31/05/13
Loans
Keywords: Food industry and trade - government policy; Agricultural industries - government policy; Food industry and trade - safety regulations; Agricultural industries - safety regulations; Food -safety measures